Development Model Of Indonesian National Health Insurance (BPJS) Flow Process At Hospital Hermina Ciruas Using Lean Hospital Approach - Royyadi Chandra; Nofierni Nofierni; Mus Aida (Journal of Multidisciplinary Academic, 2021)
This study aimed to discuss the flow of outpatient care process of Indonesian National Health Insurance (BPJS by customer perception and standards time at Hermina Ciruas Hospital using Lean Hospital approach. In order to achieve the result, we obtain empirical evidence of the outpatient service process and provide proposed improvements from in-depth interview in outpatient BPJS. In addition, we proposed qualitative by using time-motion studies with observation method and in-depth interview in outpatient BPJS. Here the research was carried out in an outpatient installation at Hermina Ciruas Hospital with data analysis using lean hospital approach (Visio software device). The limitations in the process of this study subjectivity in observation collection of inevitable data due to, the calculation of time in each related unit is carried out by the researchers themselves. The results show average patient service process time is 299 minutes with the assessment of activity value added 26 minutes with the assessment of non-value with activities 273 minutes.it’s identifies waste in the outpatient service process. The findings on the processing data of outpatient services BPJS is still waste and amount of non- value added is poor. Therefore, the improvement efforts are needed for service efficiency on BPJS performance. The proposed improvements through the application of future state value stream map with, proposed blueprint of BPJS outpatient services, socialization of outpatient registration using Hermina mobile app (will get the ticket code used for activation at the queue counter), and discipline the presence of doctors. Keywords : lean hospital, process flow, waiting time, outpatient